2015
DOI: 10.1111/ajgw.12137
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nitrate uptake in Sauvignon Blanc and Chardonnay grapevines depends on the scion and is affected by the rootstock

Abstract: Background and AimsNitrate is a major form of inorganic nitrogen present in cultivated soils; however, information on the mechanisms responsible for uptake of the anion in grapevines is scarce.\ud \ud Methods and ResultsThe response to external nitrate was studied in two clones of the cultivars Chardonnay and Sauvignon Blanc. Grapevines, own-rooted or grafted on the two rootstocks SO4 and K5BB, were grown in nutrient solution and, after a period of nitrogen (N)-deprivation, exposed to 0.2 or 1mmol/L nitrate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
(56 reference statements)
3
40
0
Order By: Relevance
“…Studied simultaneously in this work, we showed that vine N status had a greater impact than grapevine variety on the content of these metabolites. In fact, N absorption and/or assimilation is largely determined by the genotype of the plant to which it is related (Stines et al, 2000;Tomasi et al, 2015). This observation highlights the importance of terroir and the interaction between its components on the synthesis of 3SH precursors.…”
Section: Discussionmentioning
confidence: 95%
“…Studied simultaneously in this work, we showed that vine N status had a greater impact than grapevine variety on the content of these metabolites. In fact, N absorption and/or assimilation is largely determined by the genotype of the plant to which it is related (Stines et al, 2000;Tomasi et al, 2015). This observation highlights the importance of terroir and the interaction between its components on the synthesis of 3SH precursors.…”
Section: Discussionmentioning
confidence: 95%
“…In fruit crops, such as grapes, nitrate uptake is favored by the presence of rootstocks and the characteristics of the scion. The overall nitrate acquisition is affected by low affinity nitrate uptake and efflux from the root cells [44]. Grafting mini-watermelon onto rootstocks increased the activity of nitrate reductase under different levels of nitrogen supply [30].…”
Section: Discussionmentioning
confidence: 99%
“…ex Tanaka), di erent C. reshni ff K transporters have been identi ed in modifying ion uptake and fi transport to the scion, suggesting that rootstocks possess e cient high-ffi a nity K ffi + uptake systems that supply K + for growth even at very low K + concentrations ( ). Caballero et al, 2013Tomasi et al (2015 a rmed that grape rootstocks (Chardonnay ffi and Sauvignon Blanc cultivars) improved nitrate uptake by a ecting ff the low-a nity nitrate transporter gene activity. In pear ( ffi Pyrus betulaefolia) rootstock plants,…”
Section: Ion Accumulation In Grafted Plantsmentioning
confidence: 99%